Citizenship Education and Religious Literacy - Hookway, Susanna (2000)
CONSENSUS IS INADEQUATE as a basis for values in the framework for Citizenship Education in Secondary Schools in England. In contrast, Religious Education has a distinctive contribution to make through giving students an informed vision based on religious literacy. This is discussed with reference to ‘capital letter words’ which are invested with meaning by coherent world-views. RE gives pupils points of reference beyond consensus, enabling them to understand both their own and other world-views, equipping and motivating them to live as effective citizens. The Warwick Project and the Stapleford Project are evaluated as examples of this contribution.